The Indonesian provincial governments’ post-reformation good governance quality: A PCA approach - Khairudin Khairudin; Rahmawati Rahmawati; Jaka Winarna; Evi Gantyowati (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to assess the quality of post-reformation good governance implementation in 34 Indonesian provincial governments using the Principal Component Analysis (PCA) method. Specifically, the method determines the governance index sourced from the KNKG covering democracy, transparency, accountability, legal culture, and fairness and equality principles. The findings show that (1) there are 26 or 76.47% provincial governments with “good” good governance quality and 8 or 23.53% provincial governments with “adequate” good governance quality; (2) Indonesian provincial governments tend to exhibit fluctuating but downward performance (although still in the “good” category); (3) Bali Province is the best province in implementing good governance, while North Maluku Province is the worst province in implementing good governance in Indonesia; (4) the Kalimantan region is the region with better governance implementation quality in Indonesia, while the Maluku region exhibits the poorest performance. Our empirical findings underscore the importance of stakeholders’ commitments and synergy in improving good governance quality.